The singing activity of the Yellowhammer (Emberiza citrinella) under traffic noise around highways - Ritz-Radlinská, Aneta; Barták, Vojtěch; Hodačová, Lenka; Maidlová, Kristýna; Zasadil, Petr (Frontiers in Ecology and Evolution, 2023)
Steadily increasing human population is changing the environment in many ways. One of the most disturbing impacts is the development of anthropogenic noise pollution connected to ever-growing traffic intensity. The road network can have both positive and negative effects on biodiversity and populations. Many bird species use acoustic communication to establish and maintain their territories and for intra-pair and adult–young communication. Noise pollution can impact negatively on breeding success and biorhythm if this communication is masked by noise and the individuals must adjust their singing activity. Yellowhammer (Emberiza citrinella) is a common bird species of agricultural landscapes whose population is declining due to agricultural intensification. It is found also in habitats near highways with forest steppe-like characteristics, where it is affected by the high levels of anthropogenic noise pollution. This study aimed to determine how this species adapts to noise from highway traffic by adjusting its singing activity. The influence of locality type, immediate and long-term impact of traffic noise on the average and total length of song sequences in the birdsong, and influence on the total number of recorded song sequences during the second hour after sunrise were evaluated in this study. Our results showed that Yellowhammer’s singing activity changed in localities close to highways compared to agricultural landscape. With increasing long-term traffic intensity on highways, song duration and number of strophes of the Yellowhammer song was decreasing. The present traffic intensity led to later onset of dawn chorus and decreasing strophe length with increasing number of passing vehicles. Furthermore, in the agricultural landscape, Yellowhammer’s song duration and the number of syllables increased with increasing distance from the nearest road.